Liquidity Management by Effective Debt Collection: a Statistical Analysis in a Small Industrial Enterprise - Sokołowska, Ewelina; Wiśniewski, Jerzy (Ekonomika, 2015)
The financial viability of small companies depends on their ability to meet sales demands and collect receivables from the sales of goods and provision of services. The efficiency of debt recovery plays the fundamental role in determining the liquidity of a small business. Shortages of cash in the company are rarely subsidised not from external sources but most often from the owner’s own funds that such shortages are made up, including the amounts previously accumulated as a result of the so-called excess liquidity.The main purpose of the article is the hypothesis that application of statistical analysis in liquidity management can be a useful tool in effective debt collection in an enterprise.We looked at the monthly or short-term liquidity of a small business and its impact on the defined performance metrics of debt collection. The analytical tool is a dynamic econometric model that describes the impact of the efficiency of recovery for liquidity in small business.
Keywords: econometric methods; small business; statistical analysis; debt collection; liquidity management